Secondary research: information sources and methods - Kamins, Michael A.; Stewart, David (Beverly Hills: Sage Publications, 1985)
Popular in its first edition as a guide for readers to finding secondary sources, obtaining the sources, and evaluating and integrating the information from various sources to answer specific research questions, Secondary Research has been revised to give the latest information on computer-based storage and retrieval systems. The second edition features expanded coverage of computer-based information, including a new chapter on CD-ROM products and updated coverage of on-line information search services. In addition, the book includes how to do secondary analysis, information on specific sources such as commercial and government sources and examples of information searches.
Keywords: Investigación